2018
DOI: 10.1007/s10266-018-0345-6
|View full text |Cite
|
Sign up to set email alerts
|

Complications of a poly-l-lactic acid and polyglycolic acid osteosynthesis device for internal fixation in maxillofacial surgery

Abstract: The purpose of this study was to retrospectively evaluate and examine the incidence of complications using poly-L-lactic acid and polyglycolic acid (PLLA/PGA) copolymer plate system in maxillofacial osteosynthesis. The retrospective study included 87 patients (50 men, 37 women), who needed maxillofacial surgery. We examined the proportion of complications and their factors from clinical data. A comparison was also made for plate decomposition using the molecular weight of the plate without plate exposure and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 19 publications
0
31
0
2
Order By: Relevance
“…Copolymers of l -lactide and glycolide (PLGA) have been used extensively owing to the wide range of physiochemical properties of the components. Lactosorb ® (Biomet Inc., Jacksonville, Florida, USA) is a copolymer of PLLA (82%) and PGA (18%) [19] , [29] , [30] , [31] . RapidSorb ® (DePuy Synthes CMF, West Chester, PA, USA) is composed of the same polymers in almost the same ratio of 85:15; both these products are only ideal for mid-face and maxillary osteosynthesis (to date, limited approval has been obtained in Japan) [32] .…”
Section: Variety Of Bioresorbable Osteosynthesis Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Copolymers of l -lactide and glycolide (PLGA) have been used extensively owing to the wide range of physiochemical properties of the components. Lactosorb ® (Biomet Inc., Jacksonville, Florida, USA) is a copolymer of PLLA (82%) and PGA (18%) [19] , [29] , [30] , [31] . RapidSorb ® (DePuy Synthes CMF, West Chester, PA, USA) is composed of the same polymers in almost the same ratio of 85:15; both these products are only ideal for mid-face and maxillary osteosynthesis (to date, limited approval has been obtained in Japan) [32] .…”
Section: Variety Of Bioresorbable Osteosynthesis Materialsmentioning
confidence: 99%
“…The copolymer is structured to provide adequate strength for 6–8 weeks and for a complete resorption time of 12–18 months, those of which products are really feasible in a clinical application for midfacial osteosynthesis as secure and rapid bioresorbable materials, and such plate systems [8] , [9] , [19] , [29] . The recent retrospective clinical study by Sukegawa et al [30] elucidated and stressed the feasibility of PLLA/PGA copolymer plate systems in maxillofacial osteosynthesis with relatively small minor postoperative complication rates. It is metabolized via the citric acid cycle and is eventually excreted by the lungs as carbon dioxide and water [31] , [32] , [33] .…”
Section: Variety Of Bioresorbable Osteosynthesis Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the studies did not demonstrate significant differences in postoperative complications, absorbable polymers are mechanically weaker, and their degradation process through hydrolysis resulted in acidic elements, which can increase infections and bone resorption osteoclasts activation. The findings indicated that the use of PLLA and PGA might not be applicable for clinical applications, and the search for other degradable materials is warranted [ 14 , 73 , 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, investigators may have misunderstood the concept of inertia of the metals implanted into the human body over the past few decades, since some metals used for bone fixation purposes are nobler than others. However, after implantation, these metals are subjected regularly to mechanical, electrochemical, and temperature alterations, which have resulted in complications, such as infection, metal hypersensitivity, and foreign body reactions [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%